First Outbreak of Nosocomial Legionella Infection in Term Neonates Caused by a Cold Mist Ultrasonic Humidifier - Yiallouros, Panayiotis K.; Papadouri, Thalia; Karaoli, Christina; Papamichael, Elena; Zeniou, Maria; Pieridou-Bagatzouni, Despo; Papageorgiou, Georgios T.; Pissarides, Nicolas; Harrison, Timothy G.; Hadjidemetriou, Andreas (Clinical infectious diseases, 2013)
Background. To date, all descriptions of legionellosis in neonates have emerged from a small number of isolated case reports in newborns with unusually severe pneumonia. In December 2008, a large outbreak of Legionella infection occurred in term neonates in Cyprus, providing new information on the epidemiological and clinical features of Legionellosis in this age group. Methods. An environmental investigation was performed at a small private hospital where the infected neonates were delivered. The medical records of the infected neonates were retrospectively reviewed to obtain clinical data on presentation, complications, and course of disease. Results. Nine of the 32 (28%) newborns who were exposed to the contaminated source at the private nursery were infected with Legionella. Six subjects had pulmonary infiltrates, but in 3 cases there were no abnormal radiological findings and clinical presentation was mild. In 4 neonates, pulmonary infiltrates at presentation were bilateral and extensive and 3 died, conferring a mortality rate of 50% in subjects with pulmonary infiltrates and an overall mortality of 33.3%. Legionella pneumophila serogroup 3 was recovered in neonatal biological samples, although in some patients there was implication of a second strain, serogroup 1. It was determined that the neonates were infected while in the nursery at the private hospital by aerosol produced by a recently installed cold-mist humidifier that was filled with contaminated water. Conclusions. Use of humidifiers in nursery units must be avoided as the risk of disseminating Legionella in neonates is very high. In neonates legionellosis should be suspected when signs of infection first appear and take an unusual course, even when no pulmonary infiltrates appear.